Control Of Mini Autonomous Surface Vessel. - Zainal Abidin, Zulkifli; Arshad, Mohd Rizal; Ngah, Umi Kalthum; Ong, Boon Ping (2010)
This paper presents an initial development stage of mini Autonomous Surface Vehicles (ASVs). The ASVs named Drosobot is being developed for hydrographic survey on lakes.